(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Finding appropriate mechanisms for the state to adequately confront certain criminal offenses is manifested through the prescription of various special investigative actions. This paper deals with the institute of an agent provocateur as a person acting under the alias in a criminal environment and whose knowledge of relevant facts from that area has a significant place in bringing to justice the perpetrators of criminal offenses later in the proceedings. After the introductory part, the author will present the national regulation of this institute in the Republic of Serbia, with an overview of the specifics of the Anglo-Saxon and Continental legal system. Comparing legislations will provide an overview of normative regulation, basic legal requirements and practical application of this institute, with an interpretation of the problem of committing crimes by an agent provocateur. The paper will examine both criminal material and process aspect of the institute of agent provocateur, through the framework for its engagement, the type of criminal acts for which it can be engaged, the principle of subsidiarity, and other issues that may arise as controversial in its engagement. Special attention was devoted to the objectives of determining this particular special investigative action and examining the agent provocateur as a witness. Finally, concluding observations are made, with a comparative approach.